(untitled) (Journal of Nepal Geological Society, 2023)
Both tectonic activity and geological environment such as faulting and shearing in the rock mass influences the in-situ stress condition in the rock mass. The large-scale earthquakes cause both accumulation and sudden release of strain energy resulting the changes on the magnitude and direction of the in-situ stresses. This is the case in the Himalayan region, where the tectonic movement is active and periodic dynamic earthquakes are common. This manuscript assesses the influence of local shear faults on the in-situ stress condition along the pressure tunnel of Upper Tamakoshi Hydroelectric Project in Nepal. For this a 3D numerical modeling is carried out to assess potential changes in the magnitude of in-situ stresses, in particular the magnitude of minimum principal stress, due to dynamic loading (earthquake).